Salmoneus shojaei, a new species of mangrove-dwelling alpheid shrimp (Decapoda: Caridea) from Iran - Ashrafi, Hossein; Anker, Arthur; Ďuriš, Zdeněk (Zootaxa, 2022)
During a survey of the mangrove infauna on the Iranian side of the Persian Gulf and the Gulf of Oman several specimens of a new alpheid shrimp, Salmoneus shojaei sp. nov., were collected around pneumatophores of mangrove trees, mostly in association with the larger burrowing snapping shrimps of the genus Alpheus Fabricius, 1798. The new species appears to be a member of the S. gracilipes species group and is morphologically closest to S. colinorum De Grave, 2004 and S. alpheophilus Anker & Marin, 2006. However, a unique combination of morphological characters, such as the carapace without rostral carina, the unarmed ischium of the major cheliped, the armed ischia of the minor cheliped and second pereiopod, the very slender dactyli of the fourth and third pereiopods, and the posterior margin of the telson with a deep U-shaped notch, distinguishes the new species from all other members of the S. gracilipes group. In addition, S. shojaei sp. nov. presents a diagnostic, albeit very faint, banding of the pleon, which separates it from most other species of the S. gracilipes group with known colour patterns. A DNA barcode (a partial fragment of the mitochondrial gene, CO1), as well as partial fragments of the mitochondrial 16S rRNA and the nuclear H3 genes, are provided to genetically characterise the new taxon.